EFL Students' Critical Thinking and Moderation Awareness Through Reading Multicultural Texts - Anzar Agus; Hanafi Pelu; Fadilah Binti Zakaria (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
This study aims to analyze the relationship between critical thinking skills and moderation awareness among third-semester EFL students through their engagement with multicultural reading texts in an Indonesian university context. This study employs a qualitative research method with an ethnographic approach, drawing on in-depth semi-structured interviews, classroom observation, and document analysis as primary data collection instruments. Data validity was ensured through triangulation, enabling a contextually rich and methodologically rigorous interpretation of students' experiences. Participants were third-semester EFL students engaged with multicultural reading tasks specifically designed to elicit critical reflection on diverse cultural, religious, and ideological perspectives prevalent in contemporary society. The findings reveal that engagement with multicultural texts generates cognitive and affective dissonance that, when mediated by critical thinking scaffolds and guided classroom discussion, produces measurable attitudinal shifts consistent with moderation awareness. Students demonstrated growing capacities for source evaluation, bias recognition, perspective-taking, and intellectual autonomy—competencies that jointly constitute the cognitive and attitudinal infrastructure of moderation. The study concludes that EFL reading instruction, when intentionally designed around critical pedagogy and diverse multicultural texts, constitutes a viable and academically rigorous vehicle for developing moderation competency in Indonesian higher education.